Using a One Health case-based investigation for improved control of brucellosis in Isiolo, Kenya - Karlsson, P.A.; Persson, C.; Akoko, James M.; Bett, Bernard K.; Lundkvist, Å.; Lindahl, Johanna F. (Frontiers Media, 2021)
Brucella is a highly pathogenic bacteria endemic in Kenya, and in spite of its severity in humans, the highly inadequate Febrile Antigen Brucella Agglutination Test (FBAT) remains a primary tool for its diagnosis. Blood samples were collected from febrile patients in Kinna health center and screened by the local routine. Milk samples were purchased from local milk hawkers and analyzed for Brucella antibodies using the milk ring test (MRT). The MRT-positive milk was traced to farms, and lactating cattle were sampled for milk and blood. Milk was MRT-tested and the serum was analyzed using the Rose Bengal test (RBT) and iELISA. Available patient and farm samples were stored on FTA cards for qPCR analyses. Despite a limited sample size, our study, in line with previous reports, shows a low diagnostic sensitivity (67%) and specificity (40%) of FBAT when compared to qPCR. As many as 48% of the raw bulk cattle milk samples were MRT-positive for Brucella antibodies and 60% of cattle on three visited farms were IS711 qPCR-positive. This case-based One Health investigation confirms the suspected Brucella presence, suggesting a targeted vaccination at high-prevalence farms, urgent interventions on milk safety, and a re-evaluation of the diagnostic and treatment regimen.